Let's simplify each expression using the Power Rule of Exponents, which states that \((a^m)^n = a^{m \cdot n}\).
-
For the expression \((6^2)^4\): \[ (6^2)^4 = 6^{2 \cdot 4} = 6^8 \]
-
For the expression \((73^4)^5\): \[ (73^4)^5 = 73^{4 \cdot 5} = 73^{20} \]
-
For the expression \((78^8)^6\): \[ (78^8)^6 = 78^{8 \cdot 6} = 78^{48} \]
-
To simplify the expression \((12 \times 12 \times 12) \times (12 \times 12 \times 12)\), we can count the total number of 12's: \[ (12^3) \times (12^3) = 12^{3 + 3} = 12^6 \]
-
For the equation \((16^x)^6 = (16^{18})\), we use the Power Rule: \[ 16^{x \cdot 6} = 16^{18} \] This implies: \[ x \cdot 6 = 18 \] Now, solve for \(x\): \[ x = \frac{18}{6} = 3 \]
In summary:
- \(6^8\)
- \(73^{20}\)
- \(78^{48}\)
- \(12^6\)
- \(x = 3\)